Biodiesel : Growing a new energy economy - Pahl, Greg (Chelsea Green Pub., 2005)
As the politics of energy grow bleak, visionary entrepreneurs in the biofuels industry may well become society's next great hope. Rudolf Diesel designed his engine to run almost anywhere, using almost any fuel, and renewable fuels made from vegetable and other oils (foreseen by Diesel in 1912) are finally coming into their own. In this book, Greg Pahl delves into the history of the biofuels industry. He assesses its recent successes and current shortcomings, and estimates its future.--From publisher description.